2015
DOI: 10.1159/000441785
|View full text |Cite
|
Sign up to set email alerts
|

Use of Oral Misoprostol for Cervical Priming before Hysteroscopy: A Randomized Comparison of Two Dosages

Abstract: Objective: The study aims to compare the safety and effectiveness of 200 and 400 µg of oral misoprostol for cervical priming before hysteroscopy. Methods: A double-blinded randomized study included 70 patients scheduled for hysteroscopy in a Lebanese University Hospital. Two dosages of oral misoprostol (200 or 400 µg) were randomly distributed to these patients 1 h before surgery under general anesthesia. Subjective assessment of the ease of dilatation, size of the first used Hegar, cervical injuries, bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Kesrouani et al reported in their study abnormal vaginal bleeding (40%) as most common indication followed by polyps (33%), myoma (13%), endometrial thickening (10%). 7 Study done by Ayyad et al had primary infertility (80%) as main indication for hysteroscopy. 8 Similarly study conducted by Al Hilli et al documented irregular vaginal bleeding (48.9%) followed by infertility (22.7%) as an indication of hysteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Kesrouani et al reported in their study abnormal vaginal bleeding (40%) as most common indication followed by polyps (33%), myoma (13%), endometrial thickening (10%). 7 Study done by Ayyad et al had primary infertility (80%) as main indication for hysteroscopy. 8 Similarly study conducted by Al Hilli et al documented irregular vaginal bleeding (48.9%) followed by infertility (22.7%) as an indication of hysteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…When we consider the administration of misoprostol we believe that route and schedule are appointed correctly, as illustrated in the Materials and Methods section. Some studies have indicated that a lower dose of 200 microgram might demonstrate a similar effect . Furthermore, side effects might occur less frequently when misoprostol is administrated vaginally instead of orally .…”
Section: Discussionmentioning
confidence: 99%
“…As Mr Kesrouani correctly points out, adverse effects occurred significantly more often in this group compared with placebo: more nausea (17% [misoprostol] versus 11% [placebo]) as well as abdominal pain (24% [misoprostol] versus 15% [placebo]) . His dose‐finding study was able to demonstrate a relation between dosage and adverse effects: higher rates of nausea (11% [400 micrograms] versus 6% [200 micrograms]) and abdominal pain (25% [400 micrograms] versus 13% [200 micrograms]) …”
mentioning
confidence: 93%
“…We would like to take the opportunity to thank Mr Kesrouani for his positive response to our paper, published in the January issue of BJOG . We referred to his thorough, dose‐finding randomised trial in our discussion, regarding the possibility of using a lower dose of misoprostol …”
mentioning
confidence: 99%